Differential Contribution of Adeno-Associated Virus Type 2 Rep Protein Expression and Nucleic Acid Elements to Inhibition of Adenoviral Replication in cis and in trans - Weger, Stefan (J Virol, 2014)
The helper-dependent adeno-associated virus type 2 (AAV-2) exhibits complex interactions with its helper adenovirus. Whereas AAV-2 is dependent on adenoviral functions for productive replication, it conversely inhibits adenoviral replication, both when its genome is present in trans after coinfection with both viruses and when it is present in cis, as in the production of recombinant adenovirus (rAd)/AAV-2 hybrid vectors. The notion that AAV-mediated inhibition of adenoviral replication is due predominantly to the expression of the AAV-2 Rep proteins was recently challenged by successful Rep78 expression in a rAd5 vector through recoding of the Rep open reading frame (ORF). We closely analyzed the relative contributions of AAV-2 nucleic acid elements and Rep protein expression to the inhibition of adenoviral replication in both of the above scenarios. When present in cis, a sequence element in the 3′ part of the rep gene, comprising only the AAV-2 p40 promoter and the AAV-2 intron sequence, which we termed the RIS-Ad, completely blocks adenoviral replication. p5/p19 promoter-driven Rep protein expression, on the other hand, only weakly inhibits rAd/AAV-2 vector propagation, and by inactivation of the RIS-Ad, it is feasible to generate first-generation rAd vectors expressing functional Rep proteins. The RIS-Ad plays no role in the inhibition of adenoviral replication in trans in a model closely mimicking AAV-2–Ad coinfection. In this case, expression of the Rep proteins is required, as well as the presence of an amplifiable inverted terminal repeat (ITR)-containing template. Thus, very different AAV-2 elements and mechanisms are involved in inhibition of adenoviral replication during rAd/AAV-2 vector propagation and after Ad-AAV coinfection. IMPORTANCE This is the first study to systematically compare the contributions of AAV-2 protein expression and AAV-2 nucleic acid elements to the inhibition of adenoviral replication in rAd/AAV-2 hybrid vector generation and in AAV-2–adenovirus coinfection. This study shows that the two inhibitory processes are very different with regard to AAV-2 functions and the mechanisms involved. Whereas inhibition of rAd/AAV-2 hybrid vector propagation mostly involves a 3′ nucleic acid element in the rep gene, inhibition of an adenoviral genome in trans requires the Rep proteins and the AAV ITRs. These findings have important implications both for a basic understanding of the AAV replication cycle and for generation of rAd/AAV-2 hybrid vectors expressing the nonstructural and structural proteins of AAV-2.